Translation Strategies and Equivalence in Formal Document Translation: A Study of UNESCO Agreements - Syafran, Ahmad; Roselani, Ni Gusti Ayu; Octavianti, Dinda Sekar; Adawiyah, Alfina Robi’ah; Ginola, David (Universitas Pendidikan Mandalika, 2024)
This research investigates translation strategies and equivalence in translating Indonesian cultural terms in UNESCO agreements into English. The study aims to explore how translation strategies are adapted to address challenges in formal document translation, specifically considering the cultural terms and norms present in UNESCO agreements. Using a qualitative descriptive method, purposive sampling was utilized to select formal documents from the Ministry of Education and Culture's website and UNESCO's official site, yielding English and Indonesian versions of agreements on intangible heritage preserved by UNESCO. With Newmark's theories on strategies and equivalence, the findings reveal the dominant translation strategies used. The couplets strategy is the most frequently used, with a usage rate of 27.27% out of 143 data points. The transference and loan word strategy is the second most common, with a usage rate of 17.48%. The equivalences used include Functional and Descriptive Equivalence (each 14.69%) and Cultural Equivalence (9.79%). These findings offer insights that enhance the quality of cultural translation across languages. The implications highlight the need for translators to have nuanced skills in navigating cultural disparities for accurate cross-cultural communication. Further research opportunities exist in analyzing broader document types and different language pairs to expand understanding of preserving cultural elements through translation strategies and equivalence.